Improving the anti-solid tumor efficacy of CAR-T cells by inhibiting adenosine signaling pathway. (1st January 2020) - Li, Na; Tang, Na; Cheng, Chen; Hu, Tao; Wei, Xiaofei; Han, Weidong; Wang, Haoyi
ABSTRACT: Chimeric antigen receptor T (CAR-T) cell therapy has been applied successfully in treating hematologic malignancies; however, it shows very limited efficacy in treating solid tumors. Adenosine is one of the key immunosuppressive metabolites in tumor microenvironment (TME) of solid tumors. Although the effect of adenosine has been well studied using mouse CAR-T cells, its effect on human CAR-T cells has not been fully elucidated. In particular, there was no evaluation of the CAR-T cells with blocked adenosine signaling in tumor xenograft animal model, which is essential for determining the feasibility of future clinical trials. In this study, we found the expression of A2a receptor ( A2AR ) and A2b receptor ( A2BR ) both upregulated in human-derived CAR-T cells, and only A2AR was responsible for adenosine-induced impairment of CAR-T cell function. Disrupting A2AR gene in human CAR-T cells with CRISPR-Cas9 increased the anti-tumor function and prevented the exhaustion of CAR-T cells in vitro . Furthermore, CRL5826-CDX model and two patient-derived xenograft solid tumor models were applied to evaluate the efficacy of A2AR knock-out CAR-T cells, which showed superior capability of inhibiting tumor growth. Taken together, these results demonstrate that A2AR knock-out CAR-T cells have the potential of being an improved CAR-T cell therapy in treating solid tumors.